2008
DOI: 10.4003/0740-2783-24.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Threatened Bliss Rapids snail's susceptibility to desiccation: Potential impact from hydroelectric facilities

Abstract: Water levels in the regulated Snake River, southern Idaho, U.S.A. can fluctuate daily and seasonally due to hydroelectric demands. The federally listed threatened Bliss Rapids snail, Taylorconclia serpenticola Hershler et al., 1994 (Family: Hydrobiidae), survives in and near these fluctuation zones. Remaining T. serpenticola populations occur only in sections of the Snake River that are impacted by these hydroelectric facilities and associated springs. Because effects of rapid draw-down in fluctuation zones on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…However, this requires anaerobic respiration, which is inefficient (McMahon, 1988;Byrne et al, 1990). For instance, additional experiments on the effect of size classes of D. rostriformis bugensis and M. leucophaeata showed that smaller individuals died faster than larger individuals, which agrees with other molluscan studies (Iwasaki, 1997;Paukstis et al, 1999;Montalto & Ezcurra de Drago, 2003;Richards & Arrington, 2008;Havel, 2011;Van Leeuwen & Van der Velde, 2012). In addition, aerial respiration affects the acid-base balance, ion regulation and excretion (Byrne & McMahon, 1991).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…However, this requires anaerobic respiration, which is inefficient (McMahon, 1988;Byrne et al, 1990). For instance, additional experiments on the effect of size classes of D. rostriformis bugensis and M. leucophaeata showed that smaller individuals died faster than larger individuals, which agrees with other molluscan studies (Iwasaki, 1997;Paukstis et al, 1999;Montalto & Ezcurra de Drago, 2003;Richards & Arrington, 2008;Havel, 2011;Van Leeuwen & Van der Velde, 2012). In addition, aerial respiration affects the acid-base balance, ion regulation and excretion (Byrne & McMahon, 1991).…”
Section: Discussionsupporting
confidence: 82%
“…The spatiotemporal variability of these factors in ecosystems may affect desiccation tolerance of molluscs. Other behavioural strategies of molluscs are burial (Byrne et al, 1990) and the formation of dense overlapping layers of individuals, which create moist microhabitats that increase survival during droughts (Montalto & Ezcurra de Drago, 2003;Richards & Arrington, 2008). Moreover, desiccation tolerance is also determined by shell size of the specimens used for experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations